Effect of density of localized states on the ovonic threshold switching characteristics of the amorphous GeSe films - Ahn, Hyung-Woo; Jeong, Doo Seok; Cheong, Byung-ki; Lee, Hosuk; Lee, Hosun; Kim, Su-dong; Shin, Sang-Yeol; Kim, Donghwan; Lee, Suyoun (AMER INST PHYSICS, 2013)
We investigated the effect of nitrogen (N) doping on the threshold voltage of an ovonic threshold switching device using amorphous GeSe. Using the spectroscopic ellipsometry, we found that the addition of N brought about significant changes in electronic structure of GeSe, such as the density of localized states and the band gap energy. Besides, it was observed that the characteristics of OTS devices strongly depended on the doping of N, which could be attributed to those changes in electronic structure suggesting a method to modulate the threshold voltage of the device. (C) 2013 AIP Publishing LLC.
Keywords: TAILS